Neurotensin-like immunoreactivity after intestinal resection in the rat. Issue 9 (September 1987) - Olsen, P S; Pedersen, J H; Poulsen, S S; Yamashita, Y; Kirkegaard, P
Abstract : Neurotensin is a tridecapeptide located mainly in the distal small intestine. The present study was carried out in order to investigate the neurotensin response after proximal small intestinal resection in the rat. After resection, the median plasma concentration of neurotensin like immunoreactivity (NTLI) was unchanged compared with sham operated rats. Intragastric instillation of fat increased the plasma concentration of NTLI from 45 pmol/l (34-63) in sham operated rats to 92 pmol/l (46-121) in resected rats. No significant increase in the plasma concentration of NTLI was found after intragastric instillation of amino acids or glucose. The tissue concentration of NTLI increased significantly in the jejunum and ileum after proximal small intestinal resection, while the number of immunoreactive neurotensin cells was unchanged. This study shows that the adaptive responses in the distal small intestine after proximal small intestinal resection also involve the neurotensin producing cells.